The Construction of College Major Evaluation and Supply-Demand Docking Model - Chen, Wenyi (International Journal of Global Economics and Management, 2024)
The degree of compatibility between the supply of higher education talents and the demand for talents in economic development is a key factor in whether the regional economy can sustainably develop and whether education itself can grow healthily. Constructing a professional evaluation and supply-demand docking model for college students based on the relationship between supply and demand can scientifically conduct early warning monitoring, timely adjust professional settings, and the specifications and directions of talent training. It is also conducive to building an early warning system framework and using mathematical models to deeply analyze the entire early warning process. Achieve a comprehensive evaluation of talents and a rough prediction of their future career development.